Fire as driver of plant communities and soil properties changes in Puna grasslands in Southern Peruvian Andes - Ivon Gutierrez-Flores; Max Panca; Eduardo Oyague (Environmental Challenges)
Fire occurrence has been increasing in the high Andean grasslands due to the presence of highly flammable elements and climate change. Understanding the effects of the fires is crucial for the conservation of these ecosystems. This study aimed to determine the effects of fires on the composition, diversity, fruiting of plant species, and physicochemical characteristics of soils in high Andean grasslands over two post-fire growing seasons. We assessed ten fires, five of which occurred in 2023 (one post-fire growing season) and the other five in 2022 (two post-fire growing seasons). Ten transects were established at each study site, five in burned areas and five in unburned areas. Species composition differed between burned and unburned areas across both post-fire growing seasons. Species diversity and evenness were higher in the burned areas compared to unburned areas after two post-fire growing seasons. In both post-fire growing seasons, dry mass was higher in unburned areas than in burned areas. Herbs showed a higher percentage of individuals in the reproductive stage in burned areas, but only after one post-fire growing season. In contrast, the presence of woody individuals with reproductive structures was higher in unburned areas across both post-fire growing seasons. Regarding soils, only some parameters (organic matter, Na+, CEC, pH, available P, and K+) were affected by fires, and the direction of these changes varied between ∼ 6 months and ∼ 18 months post-fires. Our study suggests that fire severity in this type of ecosystem is low, as most soil parameters were not significantly affected. The burning of grasses may lead to increased diversity, particularly due to the enhanced fruiting of herb species. However, the recovery of woody species and biomass requires more time, which is perceived negatively by the local population.